Computational Study of Designed Peptide Analogs against Pseudomonas aeruginosa as a Possible Inhibitor of LptD Membrane Protein - Tauseef, Saba; Uddin, Reaz (Letters in Drug Design & Discovery, 2024)
Background: Pseudomonas aeruginosa is a common cause of nosocomial infection worldwide and is responsible for 18-61% of deaths alone. The organism has gained resistance to many known antibiotics and evolved into a multidrug-resistant strain. The LptD outer membrane protein of P. aeruginosa is a special target of interest due to its role in outer membrane biogenesis. Objective: The study aimed to gain an insight into how mutations affect the overall properties of antimicrobial peptides and to identify novel peptide analogs against P. aeruginosa. Methods: The peptide analogs were designed and shortlisted based on physicochemical parameters and estimated free energy change in the current study. The docking studies for wild type and shortlisted peptides were performed against LptD protein of P. aeruginosa. The toxicity, allergenicity, and solubility analyses of peptide analogs with high binding affinity to LptD were also conducted. Results: The molecular docking results indicated that peptide analogs 523M26, 523M29, 523M34, and 523M35 for AP00523 (wild type); 608M12, 608M13, 608M19, 608M31, 608M32, 608M39, and 608M43 for AP00608 (wild type); and 2858M25 for AP02858 (wild type) bound effectively with LptD membrane than their wild types. The toxicity, allergenicity, and solubility analyses revealed all these peptide analogs to be nontoxic, non-allergen, and have good water solubility. Conclusion: The binding energies predicted 523M26, 608M39, and 2858M25 bind effectively to LptD proteins than their wild type. Based on docking analysis, it was further predicted that 608M39 has an estimated binding affinity greater than L27-11, which is a known peptidomimetic inhibitor of the LptD protein.
Keywords: antimicrobial peptides